E-258 Role of vitamin d in clinical course of intracranial aneurysms – from rupture to recovery. (23rd July 2022) - Kashefiolasl, S; Leisegang, M; Brawanski, N; Funke, M; Keil, F; Hattingen, E; Hintereder, G; Badenhoop, K; Brandes, R; Seifert, V; Prinz, V; Czabanka, M; et al.
Abstract : Background: To date, there is no medical treatment to prevent subsequent progression to rupture of intracranial aneurysms and to control rupture-followed complications to improve the clinical outcome after SAH. We explored the role of Vitamin D (VitD3) status because of its known anti-inflammatory effect as a potential treatment. Methods: 25-vitaminD3 levels tested between 2017–02/2021 at admission and data of SAH patients with ruptured aneurysms were analyzed, prospectively. We correlated VitD3 status with size and number of ruptured aneurysms in admitted patients as well as with the rate of cerebral vasospasm and clinical outcome 6 months after aSAH. Results: A total of 103 patients were included in this cohort. We determined a significant association of sufficient VitD level with smaller size of aneurysms (<5mm) at the time of rupture (p<0, 001; OR 7) as well as with lower number of detected aneurysms (=1) (p<0, 001; OR 7). Sufficient VitD level at SAH onset was associated with a significant lower rate of neurological deficits at admission (Hunt&Hess grade ≤III) (p<0, 0001; OR 0, 03) or high blood volume described as Fisher Score 3 (p<0, 001;OR 7). Furthermore, patients with sufficient VitD level at hemorrhage onset had a lower risk for cerebral vasospasm (p<0, 05; OR 3, 5), specially for severe vasospasm (p<0, 05; OR 15) and delayed cerebral infarction (p<0, 01; OR 4, 2). In addition, we observed a higher chance for favorable outcome (mRS 0–2) (p<0, 01; OR 4, 6) in case of patients with normal VitD plasma level at admission. In our multivariate analysis, sufficient VitD level (≥30 ng/ml) was an significant independent factor affecting aneurysm size, number of aneurysm, developing cerebral vasospasm and the clinical outcome 6 month after SAH. Conclusion: VitD3 attenuates subsequent progression and aneurysm rupture affecting size and number of aneurysms. Furthermore, sufficient Vitamin D level decreases the rate of post SAH complications and supports the chance for favorable outcome. However, VitD-administration should be tested as optional treatment in management of patients with unruptured and ruptured aneurysms. Disclosures: S. Kashefiolasl: None. M. Leisegang: None. N. Brawanski: None. M. Funke: None. F. Keil: None. E. Hattingen: None. G. Hintereder: None. K. Badenhoop: None. R. Brandes: None. V. Seifert: None. V. Prinz: None. M. Czabanka: None. J. Konczalla: None.